Etty Hillesum - Brandt, Ria van den (2014)
The diaries and letters of the Dutch-Jewish Etty Hillesum (Middelburg 1914 - Auschwitz 1943) have received worldwide attention and inspired many readers. This book presents a transparent and concise introduction to the thought and life of Etty Hillesum. It succeeds in evoking Hillesum's testimony of life, through the reflection on her crucial themes and the use of many impressive citations from her diaries and letters. This little and refreshing handbook is based on thorough research of Etty Hillesum's legacy.